Breathing 100% oxygen during water immersion improves postimmersion cardiovascular responses to orthostatic stress. Issue 23 (16th December 2016) - Florian, John P.; Chon, Ki H.; Faes, Luca; Shykoff, Barbara E.
Abstract: Physiological compensation to postural stress is weakened after long‐duration water immersion (WI), thus predisposing individuals to orthostatic intolerance. This study was conducted to compare hemodynamic responses to postural stress following exposure to WI alone (Air WI), hyperbaric oxygen alone in a hyperbaric chamber (O2 HC), and WI combined with hyperbaric oxygen (O2 WI), all at a depth of 1.35 ATA, and to determine whether hyperbaric oxygen is protective of orthostatic tolerance. Thirty‐two healthy men underwent up to 15 min of 70° head‐up tilt (HUT) testing before and after a single 6‐h resting exposure to Air WI ( N  = 10), O2 HC ( N  = 12), or O2 WI ( N  = 10). Heart rate (HR), blood pressure (BP), cardiac output (Q), stroke volume (SV), forearm blood flow (FBF), and systemic and forearm vascular resistance (SVR and FVR) were measured. Although all subjects completed HUT before Air WI, three subjects reached presyncope after Air WI exposure at 10.4, 9.4, and 6.9 min. HUT time did not change after O2 WI or O2 HC exposures. Compared to preexposure responses, HR increased (+10 and +17%) and systolic BP (−13 and −8%), and SV (−16 and −23%) decreased during HUT after Air WI and O2 WI, respectively. In contrast, HR and SV did not change, and systolic (+5%) and diastolic BP (+10%) increased after O2 HC. Q decreased (−13 and −7%) and SVR increased (+12 and +20%) after O2 WI and O2 HC, respectively, whereas SVR decreased (−9%) after Air WI. Opposite patterns were evident following Air WI and O2 HC for FBF (−26 and +52%) and FVR (+28 and −30%). Therefore, breathing hyperbaric oxygen during WI may enhance post‐WI cardiovascular compensatory responses to orthostatic stress. Abstract : Breathing hyperbaric oxygen during a 6‐h water immersion (WI) augments postimmersion cardiovascular compensatory responses to orthostatic stress. The protection persisted for at least 1.5 h after egress from the water and was associated with higher blood pressure and vascular resistance during head‐up tilt compared with responses after WI with subjects breathing air. Further increases in blood pressure and systemic vascular resistance, yet with higher muscle blood flow, were observed after breathing pure oxygen in a hyperbaric chamber.